Treatment patterns and survival outcomes for patients with non-small cell lung cancer in the UK in the preimmunology era: a REAL-Oncology database analysis from the I-O Optimise initiative - Matthew Thompson; Laure Lacoin; Geoff Hall; Michael Snee; Sue Cheeseman; Majid Riaz; Will Sopwith; Carlos Chaib; John R Penrod; Melinda J Daumont (BMJ Open)
Objectives To report characteristics, treatment and overall survival (OS) trends, by stage and pathology, of patients diagnosed with non-small cell lung cancer (NSCLC) at Leeds Teaching Hospital NHS Trust in 2007–2018.Design Retrospective cohort study based on electronic medical records.Setting Large NHS university hospital in Leeds.Participants 3739 adult patients diagnosed with incident NSCLC from January 2007 to August 2017, followed up until March 2018.Main outcome measures Patient characteristics at diagnosis, treatment patterns and OS.Results 34.3% of patients with NSCLC were clinically diagnosed (without pathological confirmation). Among patients with known pathology, 45.2% had non-squamous cell carcinoma (NSQ) and 33.3% had squamous cell carcinoma (SQ). The proportion of patients diagnosed at stage I increased (16.4%–27.7% in 2010–2017); those diagnosed at stage IV decreased (57.0%–39.1%). Surgery was the most common initial treatment for patients with pathologically confirmed stage I NSCLC. Use of radiotherapy alone increased over time in patients with clinically diagnosed stage I NSCLC (39.1%–60.3%); chemoradiation increased in patients with stage IIIA NSQ (21.6%–33.3%) and SQ (24.2%–31.9%). Initial treatment with systemic anticancer therapy (SACT) increased in patients with stages IIIB–IV NSQ (49.0%–67.5%); the proportion of untreated patients decreased (30.6%–15.0%). Median OS improved for patients diagnosed with stage I NSQ and SQ and stage IIIA NSQ over time. Median OS for patients with stages IIIB–IV NSQ and SQ remained stable, <10% patients were alive 3 years after diagnosis. Median OS for clinically diagnosed stages IIIB–IV patients was 1.2 months in both periods.Conclusions OS for stage I and IIIA patients improved over time, likely due to increased use of stereotactic ablative radiation, surgery (stage I) and chemoradiation (stage IIIA). Conversely, OS outcomes remained poor for stage IIIB–IV patients despite increasing use of SACT for NSQ. Many patients with advanced-stage disease remained untreated.